Thermal Degradation And Mechanical Characteristics Of Sugarcane Bagasse Reinforced Biodegradable Potato Starch Composites - Jumaidin, Ridhwan; Mohd Zainel, Siti Nuraisyah; Adam, Nur Wardah; Hussin, Mohamed Saiful Firdaus; Ab Ghani, Ahmad Fuad; Mohammad Taha, Mastura; Yaakob, Mohd Yuhazri; Ahmad, Mohd Nazri; Maidin, Nurul Ain; Wahid, Mohammad Khalid; Ab Rahman, Mohd Hidayat; Osman, Mohd Hairizal; et al. (Penerbit Akademia Baru, 2021)
Global pollution due to the overwhelming usage of non-biodegradable plastics is getting severe nowadays. Hence, the aim of this paper is to develop an environmentally friendly composite material from potato starch and sugarcane bagasse. The composites were prepared by hot pressing at 145℃ for 60 min. The composites were characterized for their mechanical and thermal properties. In terms of thermal properties, thermogravimetric analysis shows that incorporation of sugarcane fiber has improved the thermal stability of the composites. Meanwhile, incorporation of sugarcane fibre from 0 to 15 wt.% has significantly improved the tensile (202.7%) and flexural (198%) strength of the composites. Scanning electron micrograph of the tensile fracture showed the fibre fracture and fibre “pull-out” from the composite. Overall, the biodegradable composites have shown improved functional characteristic than the origin material. This finding shows that this Sugarcane/Potato starch composites are potential alternative material for biodegradable product i.e. biodegradable plastic packaging.